Pemanfaatan Smartphone dalam Proses Perkuliahan yang Efektif dan Supportive: (Studi Kasus pada Mahasisiwa Pendidikan Ekonomi FKIP UHAMKA) - Muh Supendi; Didi Mulyadi (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Abstract This research aimed to find how smart phone as one of the very important tools nowadays develop learning environment which is suited with the current learners’ attitude who now can not be separated from the mobile phone. Case study research method used to investigate the research aim. The focus of this research is finding how important the smartphone in the learning process at the Pendidikan Ekonomi FKIP UHAMKA while the sub focuses are how effective the lecturers in using the smart phones during the learning process and how students response positively in using the smartphone for the shake of effective and supportive learning process. The research found that most of the students, 97% have and use smartphone in their daily lives and only less than a half number, 47% use them for the shake of education or knowledge sources. The research also found that they feel better informed when having discussion with enough resources and knowledge.